2020
DOI: 10.1016/j.artd.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intercondylar Femoral Box Cut-to-Femur Size Ratio During Posterior-Stabilized Total Knee Arthroplasty Increases Risk for Intraoperative Fracture

Abstract: Background: Iatrogenic intraoperative fractures are preventable complications in total knee arthroplasty. As press-fit fixation becomes more popular, further investigation into risk factors is needed. Some authors have suggested that smaller femurs may be at higher risk in posterior-stabilized constructs owing to industry designs trending toward larger, constant box sizes that increase the amount of bone resection relative to bone stock. Methods: Finite element analysis (FEA) was used to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Most of the prior research was based on mobile-bearing TKA. As the clinical outcomes and ROM are similar between UC and PS inserts, it is probably worth using UC instead of PS inserts in order to decrease the risk of some complications that have been associated with the use of PS designs, such as patellar clunk syndrome [7] or condyle fractures in small size femoral components [22].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the prior research was based on mobile-bearing TKA. As the clinical outcomes and ROM are similar between UC and PS inserts, it is probably worth using UC instead of PS inserts in order to decrease the risk of some complications that have been associated with the use of PS designs, such as patellar clunk syndrome [7] or condyle fractures in small size femoral components [22].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have also evaluated intra-operative iatrogenic complications during revision TKR, but there is limited data on intraoperative iatrogenic complications during primary TKR [22]. The rates of complication vary from 0.2% to 4.4%, while it depends on patient factors, the type of implants used and the surgical technique [12,[22][23][24][25]. Among them, the most frequently reported complications in the literature are iatrogenic laceration of the popliteus tendon, fractures and vascular injuries [23,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Smaller sized implants for certain implants may require box cuts proportionally larger than the total femoral volume, resulting in greater bone resection and further reducing the strength of the condylar bone 12 . In a finite element analysis, Sherman et al 19 found that constant large box sizes in current modern posterior stabilized designs lead to stress risers in small femurs due to substantially increased maximum stresses in the distal femur at trial impaction. Although increases in distal femur resection depth or lateralization of the box did not significantly increase medial or lateral stresses in average-sized and larger-sized femurs, when the same resection was performed in smaller femurs, lateral and medial stresses were increased by more than 40% 19 .…”
Section: Risk Factorsmentioning
confidence: 99%